2007
DOI: 10.1159/000101807
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Long-Term Effects of Combined Oral/Topical Antioxidant Treatment with the Carotenoids Lutein and Zeaxanthin on Human Skin: A Double-Blind, Placebo-Controlled Study

Abstract: Background: The skin is exposed to numerous environmental assaults that can lead to premature aging. Of these agents, perhaps none is more ubiquitous than the ultraviolet (UV) wavelengths of sunlight. The primary immediate defense against environmental skin damage is the antioxidant capacity of the skin. However, this defense system can be compromised by moderate exposure to UV light. Therefore, bolstering the antioxidant defense system of the skin is a potentially important strategy for reducing environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
132
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(157 citation statements)
references
References 106 publications
8
132
1
3
Order By: Relevance
“…A high concentration of antioxidants in skin care formulations allows the penetration of the epidermis and dermis. The main advantage of the topical administration when compared to the oral administration to treat and prevent skin conditions is the direct delivery of bioactive substances to the target area, thus eliminating concerns about systemic circulation Page 2 / 10 (Meinke et al, 2010;Palombo et al, 2007). The cutaneous delivery of antioxidants is a complementary and well known treatment to prevent skin aging and to avoid dermal diseases, such as skin cancer (Sander et al, 2004;Pinnell, 2003;Dreher et al, 1998;Lopez-Torres et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A high concentration of antioxidants in skin care formulations allows the penetration of the epidermis and dermis. The main advantage of the topical administration when compared to the oral administration to treat and prevent skin conditions is the direct delivery of bioactive substances to the target area, thus eliminating concerns about systemic circulation Page 2 / 10 (Meinke et al, 2010;Palombo et al, 2007). The cutaneous delivery of antioxidants is a complementary and well known treatment to prevent skin aging and to avoid dermal diseases, such as skin cancer (Sander et al, 2004;Pinnell, 2003;Dreher et al, 1998;Lopez-Torres et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent clinical trial has shown that the combined administration of zeaxanthin and lutein provides the highest degree of antioxidant protection against skin lipid peroxidation under UV stress (Palombo et al, 2007). Thus, functional synergism between zeaxanthin and lutein seems to be a general feature of biological tissues challenged with radiationinduced reactive oxygen species toxicity.…”
mentioning
confidence: 99%
“…Lutein [ 100,101] Nutri-cosmetics and cosmeceuticals available commercially as beauty pills or oral cosmetics are composed of antioxidants like lutein thus having antiaging effect. [102] Some in vitro studies have also proved the efficiency of lutein as photo protectors, they protect the skin against sunburn (solar erythema) by increasing the basal defence against UV light-mediated damage. [103] In a clinical trial designed to study the effects of lutein in skin upon five skin physiology parameters (surface lipids, hydration, photo protective activity, skin elasticity and skin lipid peroxidation -malondialdehyde) of human subjects, the results showed that it provides the highest degree of antioxidant protection.…”
Section: Skin Healthmentioning
confidence: 99%